PENGARUH MODAL, TENAGA KERJA TERHADAP PENDAPATAN HOME INDUSTRI TAPE KETAN DI KELURAHAN LADANG BAMBU KECAMATAN MEDAN TUNTUNGAN - Nugraha Fattahsyah Utama; Erlyanti; Dewi Sundari Tanjung (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This study aims to analyze whether capital and labor partially influence the income of Fermented Glutinous Rice (Tape Ketan) home industries in Ladang Bambu Village, Medan Tuntungan District. The objects of this research are the home industry entrepreneurs in the area. Data collection techniques included observation, documentation, and questionnaires. This study employed a mixed-methods approach, combining quantitative methods reinforced by qualitative analysis. The population consists of home industry practitioners in Ladang Bambu Village, Medan Tuntungan District. The sample represents a precisely selected portion of the population, comprising five tape ketan home industries located in Ladang Bambu Village.The independent variables in this study are capital and labor, while the dependent variable is the income of the home industries. The data analysis method used is multiple linear regression. The findings of this study are as follows: the capital variable (X1) contributes to the income variable (Y) because the t-statistic > t-table. It can be concluded that capital has a significant partial effect on home industry income, with the positive t-value indicating a direct (one-way) relationship between X1 and Y. Labor also has a positive effect on home industry income, where the t-statistic and the Significance (Sig.) value for the labor variable (X2) are both 3.458. Consequently, the null hypothesis (H0) is rejected as the Sig. value is 0.000 (< 0.05). This indicates that Ha is accepted, confirming that labor has a positive and significant influence on the home industry income variable (Y).